Morphology and ultrastructure of the pygidial gland of the Ant Dinoponera Austraus (Hymenoptera, Formicidae) - Billen, Johan; Brandão, Carlos Roberto F.; Paiva, Ricardo V. S. (Papéis Avulsos de Zoologia, 1994)
.